UJI VALIDITAS DAN PRAKTIKALITAS E-CHEMAGZ BERBASIS CHEMOENTREPRENEURSHIP PADA MATERI IKATAN KIMIA UNTUK MENINGKATKAN LITERASI KIMIA PESERTA DIDIK - Aspari, Nabila Tricia; Andromeda, Andromeda (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
In the era of globalization and digitalization, education is required to produce students who not only understand scientific knowledge but also possess critical thinking skills, scientific literacy, and readiness to face future challenges. One of the chemistry topics considered complex and abstract is chemical bonding; therefore, innovative, interactive, and contextual learning media are needed. This study aims to develop E-Chemagz based on Chemoentrepreneurship as a digital learning media on the chemical bonding topic for Phase F senior high school students to enhance their chemical literacy. This research utilized the Plomp development model through an educational design research approach consisting of three stages: preliminary research, prototype phase, and assessment phase. Media validity was assessed by experts, resulting in an average score of 0.9525, indicating the “valid” category. Practicality tests were conducted by teachers and students, each obtaining an average score of 0.97, which falls into the “very practical” category. The results indicate that E-Chemagz is capable of presenting the material in a visual, interactive, and applicable manner while integrating the values of chemical entrepreneurship. This media not only improves students' contextual understanding of chemical bonding concepts but also supports the development of their chemical literacy. Therefore, E-Chemagz is considered feasible to be used as an innovative digital learning media in senior high school chemistry education. ABSTRAKDi era globalisasi dan digitalisasi, pendidikan dituntut untuk menghasilkan peserta didik yang tidak hanya memahami ilmu pengetahuan, tetapi juga memiliki keterampilan berpikir kritis, literasi sains, serta kesiapan menghadapi tantangan masa depan. Salah satu materi kimia yang dianggap kompleks dan abstrak adalah ikatan kimia, sehingga diperlukan media pembelajaran yang inovatif, interaktif, dan kontekstual. Penelitian ini bertujuan untuk mengembangkan E-Chemagz berbasis Chemoentrepreneurship sebagai media pembelajaran digital pada materi ikatan kimia Fase F SMA guna meningkatkan literasi kimia peserta didik. Penelitian ini menggunakan model pengembangan Plomp melalui pendekatan educational design research yang terdiri dari tiga tahap: preliminary research, prototype phase, dan assessment phase. Validitas media diperoleh dari hasil penilaian para ahli dengan rata-rata skor sebesar 0,9525 yang menunjukkan kategori Valid. Uji praktikalitas dilakukan oleh guru dan peserta didik, masing-masing memperoleh skor rata-rata sebesar 0,97 dengan kategori sangat praktis. Hasil penelitian menunjukkan bahwa E-Chemagz mampu menyajikan materi secara visual, interaktif, dan aplikatif serta mengintegrasikan nilai-nilai kewirausahaan kimia. Media ini tidak hanya meningkatkan pemahaman konsep ikatan kimia secara kontekstual, tetapi juga mendukung pengembangan literasi kimia peserta didik. Dengan demikian, E-Chemagz layak digunakan sebagai media pembelajaran digital inovatif dalam pembelajaran kimia tingkat SMA.